Means of combating crime International terrorism - منجل سارة خميس; داود صباح سامي (Journal of Legal Sciences, 2021)
International attention to the fight against the financing of terrorism has been one of the most important systemic transformations of the modern international strategy for the prevention of the crime of terrorism. International attention to the financing of terrorism has gone through multiple periods، considering that funding has not been a priority for the international community. Which led the international community to notice that there are tools that assist terrorists, the most important of which is the financial instrument, namely finance. This has led the Security Council، the General Assembly of the United Nations and regional organizations to issue binding decisions and to develop international conventions that would And to make efforts to establish competent international bodies to combat them.